Climate change reshapes the eco-evolutionary dynamics of a Neotropical seed dispersal system - Sales, Lilian P.; Kissling, W. Daniel; Galetti, Mauro [UNESP]; Naimi, Babak; M. Pires, Mathias (Wiley, 2021)
Aim: Global changes will redistribute biodiversity, reshaping ecological interactions and ecosystem processes. The decoupling in the distribution of plants and their mutualistic seed dispersers, for instance, may have overlooked eco-evolutionary effects. How animal-dispersed plants will respond to changes in the distribution of their seed dispersers remains largely an open question. Here, we forecast the consequences of climate change and frugivory interactions for the spatial distribution and seed size evolution of a Neotropical palm species. Location: Atlantic forests of South America. Time period: Present day, end of 21st century. Major taxa studied: Thirty-two species of frugivorous birds, and a palm (Euterpe edulis). Methods: Future patterns of animal–plant co-occurrence were derived from ecological niche models, climate forecasts, projections of future forest loss, and seed dispersal simulations. We further explored the evolutionary effect of the spatial reorganization of interactions by modelling palm seed sizes as a function of changes in the distribution of frugivore traits. Results: Our models indicate that future climate change and deforestation may reduce the palm’s suitable distribution by 20%–50%. However, our simulations suggest that 66% of all remaining future suitable distribution (76,200 km2) would still be inaccessible to the palm without the active dispersal of seeds by frugivores. In addition, novel frugivore communities are projected to have smaller mean body mass and gape size (−23% and −10%, respectively), due to the loss of large frugivores, which may translate into a 6%–17% reduction of seed sizes across the palm’s remaining distribution. Main conclusions: Our projections indicate that frugivore seed dispersal may be critical to allow occupancy of future habitat by animal-dispersed plants. However, loss of large frugivores may affect trait selection regimes, creating hotspots of plant evolution towards smaller seeds. We argue that such complex dynamics emerging from species-specific responses to global change may reshape the distribution and evolution of several interacting partners worldwide.
Keywords: defaunation; dispersal simulation; downsizing effect; ecological niche models; forest loss; interaction networks; novel communities, mutualism